I English Language. Issue 1 (5th August 2021) - Kostadinova, Viktorija; Wiemann, Marco; Dreschler, Gea; Gregersen, Sune; Gyuris, Beáta; Zhong, Ai; Scott, Maggie; Anderwald, Lieselotte; Hansen, Beke; Leuckert, Sven; Kraš, Tihana; Ting, Shawnea Sum Pok; et al.
Abstract: This chapter has fourteen sections: 1. General; 2. History of English Linguistics; 3. Phonetics and Phonology; 4. Morphology; 5. Syntax; 6. Semantics; 7. Lexicography, Lexicology and Lexical Semantics; 8. Onomastics; 9. Dialectology and Sociolinguistics; 10. New Englishes and Creolistics; 11. Second Language Acquisition. 12. English as a Lingua Franca; 13. Pragmatics and Discourse Analysis, 14. Stylistics. Sections 1 and 2 are by Viktorija Kostadinova; section 3 is by Marco Wiemann; sections 4 and 5 are by Gea Dreschler and Sune Gregersen; section 6 is by Beáta Gyuris; section 7 is by Ai Zhong; section 8 is by Maggie Scott; section 9 is by Lieselotte Anderwald; section 10 is by Beke Hansen and Sven Leuckert; section 11 is by Tihana Kraš; section 12 is by Shawnea Sum Pok Ting, Ida Parise, and Alessia Cogo; section 13 is by Elisabeth Reber; section 14 is by Furzeen Ahmed.